Notes to Philosophy 167: Class 4 -- Kepler's Planetary System and the Rudolphine Tables -- Part 3. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The Achievement of Astronomia Nova: Summary Remarks.; Generally corresponds to the video segment: Class 4, Part 3.